Mitigating e-services avoidance: the role of government cybersecurity preparedness. (11th March 2019) - Abdelhamid, Mohamed; Kisekka, Victoria; Samonas, Spyridon
Abstract : Purpose: The purpose of this study is to understand why individuals choose to avoid using e-services due to security concerns and perceived risk when these factors are affected by the perceived degree of government cybersecurity preparedness against cyberattacks. Design/methodology/approach: The authors adopt the information systems success model to predict the role of government security preparedness efforts in influencing the determinants of e-services avoidance. The conceptual model includes four variables: security concerns, perceived risk of cyberattacks, perceived government cybersecurity preparedness and e-services avoidance. Data from 774 participants were used to analyze our conceptual model. Findings: First, the findings show that security concerns regarding personal information safety and perceived risk of cyberattacks are barriers to e-services use, with the former having a stronger effect. Second, the findings showed that perceived government cybersecurity preparedness significantly reduces security concerns and perceived risk of cyberattacks. Third, the post hoc group analysis between individuals with a bachelor's degree or higher versus those without a bachelor's degree showed that the effect of both security concerns and perceived risk of cyberattacks on e-services avoidance was greater for individuals without a bachelor's degree. The same relationship between perceived risk of cyberattacks and e-services avoidance was not supported for individuals with a bachelor's degree or higher. Originality/value: Extant privacy research fails to adequately examine the role of institutional factors, such as government efforts, and how these mitigate or amplify cybersecurity concerns and risks related to e-services. This research takes the first step toward addressing this limitation by examining the influence of government cybersecurity preparedness efforts on the determinants of e-services avoidance.